At What Age Do You Expect to Retire? Retirement Expectations and Increases in the Statutory Retirement Age. (June 2014) - Coppola, Michela; Wilke, Christina Benita
Abstract We analyse the extent to which an increase in the statutory retirement age affects individuals' retirement expectations. Understanding how individuals adjust their expectations is crucial to the evaluation of this policy, since retirement expectations directly affect other important decisions such as labour supply, engagement in (further) education and, of course, savings and investments. We consider the 2007 German pension reform that legislated an increase in the statutory retirement age from 65 years to 67. Our analysis is based on a longitudinal study that directly asks respondents at what age they expect to retire. Using a difference‐in‐differences approach, we look at the changes in subjective retirement expectations over time and estimate the extent to which they can be attributed to the 2007 reform. We find that the reform shifted the retirement expectations of the younger cohorts, although there is some heterogeneity in the way individuals adjusted. While there are no significant differences between men and women, lower‐educated individuals failed to revise their expectations. As these individuals usually acquire both lower pension claims and lower private savings, the fact that they have been slower in updating their retirement expectations causes concern regarding their income security after retirement.